A study of factory social compliance in Fashion 2000 Ltd./ 4 You Clothing Ltd. - Rahman, Mohsina (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.